Identitas, Tubuh, dan Media Sosial: Kritik Konsep Haecceitas Duns Scotus terhadap Degradasi Moral Digital (Pusat Riset dan Inovasi Nasional, 2026)
Nowadays, social media has shaped a new interaction space for human to communicate and access information broadly within a new reality phenomenon called the (global village), a term popularized by Marshall McLuchan. Although it open opportunities for limitless relationship, this phenomenon also frequently gives rise to several moral issues, such as consumerist culture, body exploitation, and the tendency of individuals to build self-identity based on social judgment. This situation aligns with Charles Horton Cooley’s idea., which asserts that self-identity is often formed through the perspective of others. Based on this context, this study aims to examine the relevance of the concept of haecceitas in John Duns Scotus thought as a basis for criticizing moral degradations in social media practices. This research uses a qualitative method through literature study and philosophical analysis of the digital identity phenomenon. The results of the study show that the concept of haecceitas emphasizes the uniqueness and dignity of every person as an individual who cannot be reduced by social construction or the demand of popularity on social media. This concept can serve as a basis for ethical reflection to strengthen the awareness of one’s distinctive identity and respect for the human body in the digital space.